Determinants of Critical Thinking in the AI Era: The Mediating Role of Self-Efficacy in Digital Literacy and Students’ Social Interaction - Daulay, Annisa Arrumaisyah; Asna, Atikah; Br Tarigan, Devi Eka Yulita (citeus, 2026)
The importance of critical thinking in higher education has become increasingly prominent amid the rapid advancement of digital technology and artificial intelligence. This study aims to examine the effects of social interaction and digital literacy on students’ critical thinking skills, with self-efficacy serving as a mediating variable. Employing a quantitative approach with path analysis, data were collected from 650 university students during the 2024/2025 academic year and analyzed using SmartPLS. The results indicate that self-efficacy has a significant effect on critical thinking (β = 0.455, p < 0.001) and functions as a mediator linking digital literacy (β = 0.286, p < 0.001) and social interaction (β = 0.166, p = 0.001) to critical thinking ability. Furthermore, digital literacy exerts a significant indirect effect on critical thinking through the enhancement of self-efficacy (indirect effect = 0.234, p < 0.001). These findings underscore that strengthening digital literacy and social interaction within educational curricula, along with fostering students’ self-efficacy, can effectively enhance critical thinking skills, which are essential for addressing academic and professional challenges in the digital era.